PEMODELAN KNOWLEDGE MANAGEMEN PENGUATAN KARAKTER KERJA SISWA SMK PADA INDUSTRI BERBASIS WEB - Suwarto Suwarto; Dedy Prasetya Kristiadi; Putri Rahayu (UNIVERSITAS RAHARJA, 2018)
This study aims to improve the character of industry-based work for vocational school with knowledge management methods. Knowledge management is an attempt to increase the knowledge that is useful in the team at the organization. Knowledge management is the management of an organization with a special focus on knowledge. Implementation of knowledge management with emphasis on strengthening the character of industry-based work using the web, is expected to be a solution of the character education needs for students in vocational high schools to be accepted to work according to their fields. This research will develop the model of knowledge management system and design prototype of model developed on the character of industry work to be shared to the teachers. The methodology used is to perform contingency factor analysis to get the knowledge management system model. The resulting knowledge management system model supports the Socialization, Externalization, Combination, Internalization (SECI) process.